2012
DOI: 10.1021/om3001179
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Weakly Bound Al–N Lewis Pairs by Hydroalumination of Ynamines and the Activation of Small Molecules: Phenylethyne and Dicyclohexylcarbodiimide

Abstract: Treatment of aminoalkynes (ynamines), Me3Si-CC-NR2 [NR2 = N(CH2CH2)2NMe, N(CHMe-CH2)2CH2], with dialkylaluminum hydrides, H-AlR′2 (R′ = CH2 tBu, iBu, tBu), afforded by hydroalumination the corresponding alkenyl derivatives R′2Al-(Me3Si)CC(H)-NR2 (3 to 6) in which the opposite Lewis functionalities adopted a cis-arrangement with the aluminum and nitrogen atoms on the same side of the resulting CC double bonds. Intramolecular Al–N interactions gave four-membered AlC2N heterocycles, but ring strain may cause r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 106 publications
1
57
0
Order By: Relevance
“…This property sheds an interesting light on the general character of frustrated Lewis pairs in terms of intra-and intermolecular activation and dual catalysis. In this view, the dehydrochlorination reactions reported here have similarity to earlier work of our groups, where we reported that an N/Al-Lewis pair is able to deprotonate even phenylacetylene, [20] a reaction which is absolutely inconceivable for tertiary amines.…”
Section: Quantum Chemical Calculationssupporting
confidence: 90%
“…This property sheds an interesting light on the general character of frustrated Lewis pairs in terms of intra-and intermolecular activation and dual catalysis. In this view, the dehydrochlorination reactions reported here have similarity to earlier work of our groups, where we reported that an N/Al-Lewis pair is able to deprotonate even phenylacetylene, [20] a reaction which is absolutely inconceivable for tertiary amines.…”
Section: Quantum Chemical Calculationssupporting
confidence: 90%
“…Although the majority of systems is limited to P/B or N/B pairs, the use of Al‐, C‐, or Si‐based Lewis acids emerged. Especially FLPs with Al Lewis acids have been able to add unique metal‐based reactivities to the growing repertoire: for example, the complexation of alkali metal hydrides, stoichiometric and catalytic dehydrocoupling of amine–boranes, activation of alkenes,, alkynes,, carbodiimides, isocyanates, hydrogen, CO 2 , and other carbonyl groups . Our expertise in alkaline earth metal chemistry stimulated us to expand the scope of Lewis acids with group 2 metal Lewis acids.…”
Section: Introductionmentioning
confidence: 99%
“…[10] It is an important starting compound in hydroalumination reactions [1,11] and has an interme-diate steric shielding between that of bis(tert-butyl)aluminum hydride and the commercially available diisobutylaluminum hydride which is a standard reagent in organic transformations. Its molecular structure in the solid state has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%